"The Nature of My Love Had Never Been in Doubt…" Christopher St John (1871-1960): Platonic Love and Sapphic Desire. (26th May 2020) - Mackelworth, Jane
ABSTRACT: In the early decades of the twentieth century, Christopher St John (1871-1960) wrote about passionate love and sexual desire between women, in private and published texts.  She drew on several literary, philosophical and religious traditions, predominantly Hellenism and Christianity. This article explores the role of Hellenism in her writing, particularly Platonic friendship and Sapphic desire. It suggests we reconsider the idea of there being a clear disjuncture between the nineteenth and twentieth centuries in terms of women's understanding of same-sex love and desire, and the extent to which the emergence of lesbian identity overrode earlier modes of thought and expression.